Comparison of Interfacial and Foaming Properties of Soy and Whey Protein Isolates - Abirached, Cecilia (2012)
A comparative study on the foaming properties and behavior at the air-water interface of soy and whey protein isolates were made. Foams were obtained by the method of gas bubbling. The initial rate of passage of liquid to the foam (vi) and the maximum volume of liquid incorporated to the foam (VLEmax) were determined. The destabilization process of the formed foams was analyzedby a biphasic second order equation. Measurements of equilibrium surface tension (water/air) and surface rheological properties were carried out in a dynamic drop tensiometer. The foaming capacity (vi and VLEmax) and the stability of foams prepared with the whey protein isolates (WPI) were better than those formulated with the soy protein isolates (SPI). WPI foams were more stable showing the lower values of rate constants of gravity drainage and disproportion. There were significant differences (P ≤ 0.05) in the dilatational modulus in the surface rheology measurements, which were higher at the interface with WPI, implying greater resistance of the film formed to collapse and disproportion. In conclusion, WPI formed better and more stable foams than the SPI.